ASTHENOSPHERIC FLOW AND ORIGIN OF VOLCANISM IN THE BAIKAL RIFT AREA - Lebedev S.; van der Hilst R.D.; Meier T. (My University, 2006)
The origin of low-volume, hotspot-like volcanism often observed in continental rift areas is debated, as is the nature of the flow in the mantle beneath. In this paper we assemble seismic constraints on the mantle flow below the Baikal Rift Zone. We combine new evidence from upper-mantle tomography and from a radially anisotropic shear-velocity profile measured beneath and SE of the rift with published shear-wave-splitting constraints on azimuthal anisotropy. Fast directions of azimuthal anisotropy are perpendicular to the rift on both of its sides. Stable Siberian-Platform lithosphere on the northern side extends down to 200 km; on the southern side, the lithosphere is only 60-70 km thick. This asymmetry, with the thick cratonic root forming a barrier to convective flow, inhibits a mid-ocean-ridge-like flow pattern. The radially anisotropic profile yields evidence for horizontal flow in the upper asthenosphere (60-100 km) SE of the rift but no evidence for vertical flow. These results are consistent with horizontal asthenospheric flow NW to SE perpendicular to the rift, from beneath the thick Siberian towards the thin Baikal-Mongolian lithosphere. When asthenosphere ascends from the 200-km depth beneath the craton to shallower depths beneath the rift, decompression melting of embedded veins of enriched rock can produce the hotspot-like basaltic volcanism observed. The occurrence of such veins of enriched mantle in sub-cratonic asthenosphere has been predicted by geochemical mantle models; we propose that sub-horizontal asthenospheric flow from beneath cratons is a common cause for hotspot-like volcanism in continental rift zones. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANISOTROPY; CONTINENTAL RIFT; HOTSPOT; MANTLE FLOW; PLUM-PUDDING; PLUME